Analysis of Hajj Savings Development Strategy at BPRS HK Parahyangan to Increase the Number of Young Customers - Dewi Kumalasari; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the development strategy of Hajj savings at BPRS HIK Parahyangan, with a focus on increasing the number of young customers. With the growing financial literacy of the younger generation, there is a significant opportunity to increase the number of customers from this segment. The methods used include SWOT analysis, interviews with management, and surveys of potential young customers. The research results show that product innovation, the use of digital technology, and relevant marketing strategies are key to successfully attracting young customers. Furthermore, collaboration with youth communities and digital service providers has been identified as a strategic step to enhance market penetration.